PENYULUHAN MANFAAT JUS ALPUKAT TERHADAP PENURUNAN TEKANAN DARAH IBU HAMIL DI KLINIK PRATAMA CITRA KECAMATAN DELI TUA KABUPATEN DELI SERDANG TAHUN 2022 - Purti Ayu Yessy Ariescha; Desi Fitri Ayuni; Erlina Hayati; Septa Dwi Insani; Marlen Sadrina Sitepu (Jurnal Pengabdian Masyarakat Putri Hijau, 2022)
Gestational hypertension is hypertension characterized by blood pressure ≥140/90 mmHg and proteinuria ≥300 mg/24 hours at 20 weeks of gestation. Some people choose alternative medicine to treat high blood pressure. One of them is herbal remedies, accepted by the medical community as a treatment for high blood pressure. This therapy uses herbs that have been shown to contain medicinal herbs such as antihypertensives. This activity took place from Monday to Tuesday, December 6, 2022 at Marendal Citra Clinic, Medan city. The purpose of this event was to analyze the effect of avocado juice on lowering blood pressure.Pressure in Pregnant Women, 20 pregnant women attended the event and gave pregnant women a pre- and post-examination questionnaire. . The results of this community service show that 98% of 20 pregnant women increased their knowledge of the benefits of avocado her juice on blood pressure. When taken orally, it returns to normal in prehypertension, but when prehypertension becomes prehypertension, blood pressure drops after oral administration.